Efektivitas Program Pembangunan Saluran Irigasi Sebagai Upaya Peningkatan Kapasitas Pertanian di Kalurahan Margodadi - Elsa Indah; Ferdi Nur Salatsa; Inggrit Devi Saputri; Fitriana Pujiastuti; Gerry Katon Mahendra; Bhakti Gusti Walinegoro (Universitas Kapuas Sintang, 2025)
Rural development is an effort to improve the welfare of village communities through various means such as developing the agricultural economy, developing appropriate technology, and developing infrastructure. The aim of this research is to analyze the effectiveness of the sustainable agricultural irrigation canal construction program in Margodadi Village. This research uses qualitative methods with data collection techniques of observation, interviews and literature study. This research refers to 4 aspects, namely accuracy of program targets, program socialization, program objectives, and program monitoring. Based on the results of the research that has been carried out, it was found that the four existing aspects show that the construction of irrigation canals in the Margodadi District shows significant effectiveness and has an effect on increasing agricultural capacity. It can be seen that this development program is right on target and well received by the community even though it has only been implemented in 10 of the 16 hamlets. The construction of the irrigation canal is being carried out in stages to ensure equitable development.